2020
DOI: 10.1080/17425247.2020.1776260
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing of hybrid drug delivery systems by utilizing the fused filament fabrication (FFF) technology

Abstract: The potential of fused filament fabrication (FFF) for the administration of active pharmaceutical compounds is a recent approach to develop complex and custom-made drug delivery systems (DDSs). However, the FFF technology is characterized by certain limitations, which are associated with the nature of the process, i.e., the required mechanical properties of the feedstock, as well as the thermal stability of the incorporated polymers, excipients and active compounds. Thus, hybrid DDSs have been recently introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…It has also been demonstrated that amorphization via hot-melt extrusion and subsequent FDM can produce formulations in which the drug quickly recrystallizes [44]. These limitations of FDM are starting to be addressed via the use of a combinatorial approach involving novel hybrid systems, comprising one part produced via FDM and another part produced by a different technique to overcome the shortcomings of their respective techniques [45].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that amorphization via hot-melt extrusion and subsequent FDM can produce formulations in which the drug quickly recrystallizes [44]. These limitations of FDM are starting to be addressed via the use of a combinatorial approach involving novel hybrid systems, comprising one part produced via FDM and another part produced by a different technique to overcome the shortcomings of their respective techniques [45].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, FDM provides a competent alternative to the conventional manufacturing techniques for substrates (e.g., solvent casting and injection molding), by avoiding time-demanding steps (e.g., drying) and the need for incorporating additional equipment (e.g., molds). The current approach is built on the general hybridization concept for additive manufacturing of drug delivery systems [21,22]. It has been claimed that the administration of drugs via the oral cavity may provide a dependable and useful alternative to the peroral route, as the formulation avoids the environmental challenges imposed by the segments of the gastrointestinal tract and circumvents the first-pass effect [23].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the 2D inkjet printing technology provides the potential to advance the loading of poorly soluble drugs in a medicinal formulation, following the exploitation of suitable solvents in the development of inks [6]. The inkjet printing technique has been coupled with other formulation approaches, to fabricate hybrid drug delivery systems [7][8][9].…”
Section: Introductionmentioning
confidence: 99%